1984
DOI: 10.2136/sssaj1984.03615995004800010032x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harvesting and Site Preparation on Physical Properties of Piedmont Forest Soils

Abstract: The impact of intensive forest management practices on soil bulk density, aeration porosity, and saturated hydraulic conductivity was examined to a depth of 0.3 m before harvest, after harvest, and after site preparation. Harvesting caused significant changes in soil physical properties to an average depth of 0.17 m in whole tree harvest plots and 0.22 m in skid trail plots. Disking was effective in restoring soil physical properties to preharvest levels in the upper 0.07 to 0.12 m of soil. Soil compaction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Similar to observations f?om other trafficking studies (Gent et al,1984;Burger et al, 1985), significant (P < 0.05) increases in pb were observed between pre-and post-harvest samples for many of the depth intervaltrafficking class combinations at all three sites (Table 4). Similar to other studies (Morris and Campbell, 1991), we observed that pb increased not only in skid trails but also within relatively less trafficked areas (Table 4).…”
Section: Traficking Eflectssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to observations f?om other trafficking studies (Gent et al,1984;Burger et al, 1985), significant (P < 0.05) increases in pb were observed between pre-and post-harvest samples for many of the depth intervaltrafficking class combinations at all three sites (Table 4). Similar to other studies (Morris and Campbell, 1991), we observed that pb increased not only in skid trails but also within relatively less trafficked areas (Table 4).…”
Section: Traficking Eflectssupporting
confidence: 87%
“…The 40 cm depth was chosen because previous studies in similar soils suggested timber harvesting impacts do not occur below this depth (Gent et al, 1984;Carter et al, 2000). In each sampling area, a recording cone penetrometer was used to measure soil strength at 2.5-cm increments down to a 40-cm depth.…”
Section: Lncatiotl Qf Sartrpliry Arcac and Site Distrrrl~arm-clarmmentioning
confidence: 99%
See 1 more Smart Citation
“…Release of water at soil water contents less than field capacity is controlled by particle size distribution. While some mixing of soil horizons can occur during upland forest site preparation that includes piling (Gent et al, 1984;Hoadley, 2014), the influence on particle size distribution within the profile is small compared to the influence on macroporosity. When macropores are created by tillage, the soil water release curve (soil water content plotted against soil water potential) is shifted, but the curve shape is largely retained since particle size distribution, which largely controls the shape of the water retention curve (Ghanbarian-Alavijeh et al, 2010;Zhuang et al, 2001), is not greatly affected.…”
Section: Discussionmentioning
confidence: 99%
“…In southeastern forests, bedding radically alters the forest floor by mechanically creating raised beds to plant plantation seedlings. Physical disturbance may remove organic material, therefore altering bulk density and disrupting the nitrogen cycle as well as leading to accelerated soil erosion (Fox et al 1986;Gent et al 1984;Grigal 2000;Jandl et al 2007;Jurgensen et al 1997;Mclaughlin et al 2000). Surface disruption can also cause lingering changes to soil biochemistry and microbial communities (Amaranthus et al 1989;Hartmann et al 2012).…”
Section: Soil Change In Forest Landsmentioning
confidence: 99%